Memahami Pesan Dakwah Dalam Siaran Radio dan Televisi - Kharisma Yosiyana; Erwan Efendi; Wahyu Hidayat; Muhammad Alfarizi (STIT Sirojul Falah Bogor, 2023)
This study aims to find out how to understand da'wah messages through radio and television. Understanding the message of da'wah is knowing what the Da'i conveys in oral, written, behavioral and so on is done consciously and planned without any coercion based on the Al-Qur'an and hadith. The message of da'wah is Aqidah, morals and Shari'at. With various kinds of da'wah messages that the da'I wants to convey to mad'u. then a da'I must know in advance what is needed by mad'u at this time. so mad'u also listens and can understand the missionary message conveyed by the da'i. In terms of the language conveyed, Dai also pays attention. Now a preacher must also be good at mastering this media, so he knows how to preach on radio and television so that the message of da'wah is right on target. Keywords: Understanding, Da'wah Messages, Radio and Television